2022
DOI: 10.2478/puma-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Optimal colorings of Max k-Cut game

Abstract: We investigate strong Nash equilibria in the max k-cut game on an undirected and unweighted graph with a set of k colors, where vertices represent players and the edges indicate their relations. Each player v chooses one of the available colors as its own strategy, and its payoff (or utility) is the number of neighbors of v that has chosen a different color. Such games are significant since they model loads of real-worlds scenario with selfish agents and, moreover, they are related to fundamental classes of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…In our work, we extend the main results of [10,12] since we show important properties of minimal subsets and strong deviation. Moreover, we prove that there does not exist any subsets of nodes able to increase their own payoffs simultaneously.…”
Section: Our Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In our work, we extend the main results of [10,12] since we show important properties of minimal subsets and strong deviation. Moreover, we prove that there does not exist any subsets of nodes able to increase their own payoffs simultaneously.…”
Section: Our Resultssupporting
confidence: 63%
“…The most important existing result was provided by the authors of [10,11], who showed that on undirected unweighted graphs, optimal colorings are 5-strong equilibria (5-SE), i.e., colorings in which no coalition of at most five vertices can profitably deviate. These results were extended to 7-SE by the same authors of this work [12].…”
Section: Introductionsupporting
confidence: 69%
“…We are now ready to prove the main result of the section. Note that this result was presented at the conference mentioned in the introduction [15]. Theorem 3.…”
Section: Propositionmentioning
confidence: 80%
“…Therefore, G(C) must be an isolated component of G. Now, we prove that for all the cases where a minimal strongly deviating coalition, C, has, at most, 7 vertices, the cut value increases. This result was presented at the conference mentioned in the introduction [15]. Theorem 2.…”
Section: Propositionmentioning
confidence: 83%
See 1 more Smart Citation